2013
DOI: 10.1002/srin.201200187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sulfur Addition to the High Basicity Slag on the Sulfur, Aluminum, and Cleanliness of High Sulfur Al‐Killed Molten Steel

Abstract: In the present work, the influence of sulfur addition to the high basicity slag on the Al‐killed molten steel with high sulfur content was investigated by using a vacuum induction furnace at 1873 K in MgO crucibles. CaO–SiO2–Al2O3–MgO–CaS slags were used to study the effect of high basicity slags with different CaS contents on sulfur loss, aluminum loss, and total oxygen content in the molten steel. It is shown that the sulfur content in the molten steel decreased with the time, and the addition of CaS into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Holappa et al 21) reported a thermodynamic evaluation of inclusion formation and modification in calcium treated steel transferring from ladle to tundish and mold until the steel solidified. Recently, Verma et al [24][25][26] reported a mechanism of using calcium to modify alumina and spinel inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Holappa et al 21) reported a thermodynamic evaluation of inclusion formation and modification in calcium treated steel transferring from ladle to tundish and mold until the steel solidified. Recently, Verma et al [24][25][26] reported a mechanism of using calcium to modify alumina and spinel inclusions.…”
Section: Introductionmentioning
confidence: 99%